Screening Europe in Australasia Transnational silent film before and after the rise of Hollywood - Allen, Julie K. (Exeter Studies in Film History, 2022)
Through a detailed study of the circulation of European silent film in Australasia in the early twentieth century, this book challenges the historical myopia that treats Hollywood films as having always dominated global film culture. Before World War I, European silent feature films were ubiquitous in Australia and New Zealand, teaching Antipodean audiences about Continental cultures and familiarizing them with glamorous European stars, from Asta Nielsen to Emil Jannings. After the rise of Hollywood and then the shift to sound film, this history-and its implications for cross-cultural exchange-was lost. Julie K. Allen recovers that history, with its flamboyant participants, transnational currents, innovative genres, and geopolitical complications, bringing it all vividly to life. Making ground-breaking use of digitized Australian and New Zealand newspapers, the author reconstructs the distribution and exhibition of European silent films in the Antipodes, along the way incorporating compelling biographical sketches of the ambitious pioneers of the Australasian cinema industry. She reveals the complexity and competitiveness of the early cinema market, in a region with high consumer demand and low domestic production, and frames the dramatic shift to almost exclusively American cinema programming during World War I, contextualizing the rise of the art film in the 1920s in competition with mainstream Hollywood productions.